2022
DOI: 10.21470/1678-9741-2022-0142
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Patency of Coronary Artery Bypass Conduits: An Updated Network Meta-Analysis of Randomized Trials

Abstract: Introduction The second best conduit for coronary artery bypass grafting is uncertain. The objective of this study is to determine the second best conduit according to graft patency results from randomized controlled trials using a network meta-analysis. Methods A systematic literature search was conducted for randomized controlled trials comparing the angiographic patency rate of the no-touch saphenous vein (NT-SV), the radial artery (RA), the right internal thoracic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Compared with the conventionally harvested SVG, only the radial artery [incidence rate ratio (IRR) 0.54, 95% CI 0.35–0.82] and no-touch SVG (IRR 0.55, 95% CI 0.39–0.78), but not the RITA (IRR 1.06, 95% CI 0.73–1.54) or GEA (IRR 0.98, 95% CI 0.64–1.42), were associated with significantly lower graft occlusion rates. Similar results were found in an updated network meta-analysis of 18 randomized trials including 8272 grafts at a mean angiographic follow-up of 3.5 years [18 ▪ ].…”
Section: What Is the Incidence Of Graft Failure In Contemporary Coron...supporting
confidence: 84%
“…Compared with the conventionally harvested SVG, only the radial artery [incidence rate ratio (IRR) 0.54, 95% CI 0.35–0.82] and no-touch SVG (IRR 0.55, 95% CI 0.39–0.78), but not the RITA (IRR 1.06, 95% CI 0.73–1.54) or GEA (IRR 0.98, 95% CI 0.64–1.42), were associated with significantly lower graft occlusion rates. Similar results were found in an updated network meta-analysis of 18 randomized trials including 8272 grafts at a mean angiographic follow-up of 3.5 years [18 ▪ ].…”
Section: What Is the Incidence Of Graft Failure In Contemporary Coron...supporting
confidence: 84%
“…25 The rate of RIMA graft occlusion in our study was higher than the reported rate in the literature (68 vs. 89%, respectively) that could be explained by differences in surgical technique (such as Y-grafting). 26 In our previous study, we studied 70 consecutive patients treated with CABG who underwent clinically indicated ICA after surgery with the aim of investigating the functional progression of CAD in native vessels and assessing the relationship between the preoperative angiography-derived FFR value and graft occlusion. 15 The population of this study was limited to 70 patients because ICA after CABG was an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Benedetto et al evaluated the angiographic patency of the RITA, the radial artery, and the SVG through a network meta-analysis of nine randomized controlled trials (N = 145 RITA, 871 radial arteries, 845 SVGs): at follow-up, patency rates were superior for RITA compared to the radial artery, whereas both grafts were found to be superior to the SVG [ 22 ]. A more recent network meta-analysis by Deng et al [ 23 ] of 18 trials with a total of 8272 grafts and a weighted mean angiographic follow-up of 3.5 years found that the radial artery (IRR 0.56 [0.43–0.74]) and no-touch SVG (IRR 0.56 [0.44–0.70]) were associated with reduced graft occlusion compared to the conventionally harvested SVG.…”
Section: Multiple and Single Arterial Grafting And Harvesting Methodsmentioning
confidence: 99%